Boundary layer flow and heat transfer for Maxwell fluid and viscoelastic nanofluid over a stretching sheet - Nazila, Ishak (2019)
The problem of boundary layer flow has many applications in industry and engineering field. Some of these applications are drawing of plastic films, glass fiber production, hot rolling and many others in industrial manufacturing processes. The final product requested characteristics depends on the cooling liquid used and the rate of stretching. Non-Newtonian fluids can be defined in several categories like viscoelastic, time-dependent viscosity and non-Newtonian viscosity. Such fluids like oils, ketchup, food paste, paints and colloidal solutions. The study of non-Newtonian fluids has gain great attraction due to their better performance in industrial and technological applications if compared to Newtonian fluids. In this thesis, there are two types of non-Newtonian fluids namely Maxwell fluids and viscoelastic nanofluids has been examined and proposed. There are two types of boundary conditions that will be studied in this thesis, that are prescribed wall temperature (PWT) and slip condition. The proposed model for each problem depends on the system of governing equations which along with imposed initial and boundary conditions. Suitable non-dimensional variables are then introduced and reduce the governing equations into dimensionless form. The numerical solutions of ordinary differential equations are solved by shooting method. Then, shooting method is carried out to solve the resulting system of ordinary differential equations through "build in" program in MAPLE-13 software. These solutions satisfy and asymptotic for the applied of imposed initial and boundary conditions. Numerical computations are carried out for various values of the parameters of the problems, which include the Prandtl number stretching parameters suction parameters magnetic parameter Maxwell parameters Brownian parameter thermophoresis parameter thermal radiation parameters Lewis number velocity and thermal slip parameter are considered. Comparisons of present result with previously published results are done and it is found to be in a good agreement. Numerical results presented in this study are the temperature profile, the velocity profile, the skin friction coefficient, the local heat transfer coefficient, the Nusselt number and the Sherwood number. The rises of stretching parameter and thermal characteristics are resulting on decreasing in the wall temperature and thermal boundary layer thickness. Other than that, the increasing in the Maxwell and suction parameter leads to increase on the local heat transfer while the skin friction coefficient, velocity and temperature profile become decrease. The presence of velocity slip parameter has accelerated the movement of fluid particle at surface from static to a certain velocity. This situation reduces the skin friction coefficient as well as the effect on stretching parameters.